CARACTER EDUCATION MANAGEMENT IN REALIZING THE QUALITY OF GRADUATES : (Case Study of Cikanyere Integrated Senior High School, Ciamis Regency) - Zakiyah, Maya Mariah (Indikator Pendidikan Indonesia, 2023)
This study seeks to investigate three main aspects: (1) the essence of quality education intertwined with character development, (2) a comprehensive model for planning, executing, and overseeing character education to enhance the caliber of graduates, and (3) the ramifications of implementing character education management models in achieving graduate quality. This research employs a qualitative methodology, employing a case study framework and a multicasting design. Data collection methods encompass in-depth interviews, participant observations, and document analysis. Data is examined through an interactive model involving data collection, reduction, presentation, and conclusion drawing. The findings of this study reveal that: (1) Quality education with a character emphasis embodies excellence in academic achievement and a strong sense of religious values. It places an emphasis on the integration of moral understanding, emotional resonance, and ethical action through role modeling and a systemic approach; (2) The planning model for character education is based on a holistic and integrated approach. The implementation model utilizes habituation, personal embodiment, exemplary behavior models, the integration of extracurricular and curricular activities, and the creation of a supportive learning environment. The supervisory model combines internal control mechanisms through disciplinary procedures and attitude documentation, as well as external oversight through home visits; (3) These findings carry significant implications for school policies, including character-centered curricula, tools for regulating habituation processes, and clear objectives. They also underscore the importance of a systemic and integrated character education management system for nurturing graduates with exceptional academic character and a profound sense of religious awareness, who are committed to upholding the core values of character quality.